Community Ecology of Urban Birds in Suburban Areas of Kuching and Kota Samarahan, Sarawak - Hong, Arleen (Universiti Malaysia Sarawak (UNIMAS), 2021)
Urbanisation dramatically changes the structure of bird communities, resulting in increasing of biotic homogenisation as same species, “generalists” are widespread and ubiquitous in urban landscapes. The aim of the study was to investigate the potential relationship of detailed component of urban form (i) vegetation heterogeneity, (ii) housing density and (iii) carnivore density (cats and dogs) with birds in suburb residential. Numerous studies of birds have been carried out in urban landscapes, yet most of the studies have been carried out in the temperate regions, little is known in the tropic regions. This study examines the bird species diversity in suburban area including their feeding guilds, how vegetation heterogeneity and housing density influence bird diversity. A further aim was to investigate the influence of cats Felis catus and dogs Canis familiaris on bird occurrences and survival. The density of birds and carnivores, and vegetation richness were examined in thirteen suburb residential areas of Kuching and Kota Samarahan divisions from February 2016 to February 2017 using line transects. A total of 7,851 bird observations were made, involving 34 species that representing 22 families. Six generalist species were encountered in all surveyed residential areas and four were introduced. These generalist species were either omnivores or granivores that dominated the urban bird species composition. Bird density (7.5 ind. ha-1) was elevated by the abundance of these species. This study found that bird species richness was positively related to vegetation richness and tree species richness (R2 = 0.39; R2 = 0.41, respectively). However, this vegetation richness was not significantly influence on bird density (R2 = 0.01). Housing density was not an important variable in influencing birds in suburban habitat (P = 0.91). Similarly, bird species assemblage found no significant association with carnivore density neither cats nor dogs (R2 = 0.25; R2 = 0.11, respectively). These findings are important and relevant for urban land use planning where vegetation richness is needed to be considered in order to enhance a balance habitat for the coexistence of human and avian assemblage in urban habitats.